Nursing Care of Acute Pain in Multiple Fractures with Spiritual Therapy Quantum Touch and Finger Holding: A Case Study - Dewi, Risma Eka Putri Arlyani Kusuma; Hakam, Mulia; Sutawardana, Jon Hafan; Shodikin, Mohammad (Al-Hijrah Indonesia, 2024)
Background: Multiple Fractures or broken bones are a condition where the continuity of the bones is broken in a complex manner, this is caused by trauma caused by frequent traffic accidents. Objective: To analyze the effect of a combination of non-pharmacological therapies Quantum Spiritual Touch Therapy